2019
DOI: 10.3390/polym11111782
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Antifouling Membrane Surfaces through Layer-by-Layer Self-Assembly of Lignosulfonate and Polyethyleneimine

Abstract: Lignin is the second most abundant and low-cost natural polymer, but its high value-added utilization is still lack of effective and economic ways. In this paper, waste lignosulfonate (LS) was introduced to fabricate antifouling membrane surfaces via layer-by-layer self-assembly with polyethyleneimine (PEI). The LS/PEI multilayers were successfully deposited on the polysulfone (PSf) membrane, as demonstrated by ATR-FTIR, XPS, Zeta potential measurements, AFM, and SEM. Meanwhile, the effect of the number of bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…For calculation of porosity, gravimetric analysis was done using Equation (2). Membranes were first dried at 50 • C for 3 h to remove any moisture and then weighed (W d ).…”
Section: Characterization Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…For calculation of porosity, gravimetric analysis was done using Equation (2). Membranes were first dried at 50 • C for 3 h to remove any moisture and then weighed (W d ).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…One of the major factors that govern the permeability rate for membranes is their wettability. The higher the wettability, the higher hydrophilic character, and the higher the enhanced flux rate and anti-fouling property [2]. This property is evaluated by the measurement of the contact angle.…”
Section: Surface Hydrophilicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that the success of the surface modification between the two substrates is significantly improved by increasing the hydrophilicity of membrane surfaces using methods such as grafting, chemical cross-linking, or chemical reaction of the surface. This change reduces the adsorption of foulant by inhibiting non-specific binding between the membrane surface and retained molecules, particularly proteins [ 19 , 25 ]. In fact, the ideal membranes for water purification (UF or RO) are hydrophilic semi-permeable membranes that allow for high flux while being highly selective through the membrane [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…While 3D printing, as a newly emerged technology, attracts attention from a lot of researchers as a method with which to explore new ways to fabricate polymeric devices with enhanced performance and/or new functions [1][2][3][4][5], sensors and actuators (including wearable/flexible electronic devices) still appear to be the major focus in polymer applications [1,[5][6][7][8][9][10][11][12][13][14][15]. Polymers with special features/functions, such as stimulus-responsive and shape memory [16,17], self-healing [18][19][20][21][22], and assembly [23][24][25][26][27] are being continuously developed, along with analytical/numerical studies [28][29][30], in order to capture the fundamentals for efficient and/or optimized engineering design. Of course, the above mentioned are only parts of the topics of the published papers in 2019 under this section, which focuses on polymer applications.…”
mentioning
confidence: 99%